Online hotel ratings and its influence on hotel room rates: the case of Lisbon, Portugal - Castro, Conceição; Porto Accounting and Business School of Polytechnic of Porto; CEPESE (2018)
Lisbon is one of the European Union cities that has one of the highest growth in the number of hotels. With the digital revolution travelers can easily not only compare prices but also get information about the experience of other guests which can influence prices. The aim of this paper is to analyze how prices for a hotel stay can be influenced by some quality signaling factors, as star rating and online consumer’s ratings (location, cleanliness, comfort, facilities, staff and value for money, available on Booking.com), the volume of consumer’s comments and the availability of rooms in Lisbon. For 151 hotels in Lisbon, from 3 to 5 stars, through a multiple regression model, the results suggest that hotel category, location and facilities ratings have a positive influence on hotel room rates, but higher trade-off between what clients pay and the guest hotel stay experience has a negative impact on the consumer’s willingness to pay, as well as the number of comments. Among different hotel categories, the influent factors are different. Our main findings provide signs to hoteliers to take corrective actions towards the attributes most valuable for consumers and that can provide a higher room rate premium.